Improving the Quality of Life towards Healing Long Haul Symptoms of COVID- 19 Survivors through Online Video Booklets and Gymnastics and Education - Berniyanti, Titiek; Marhazlinda, Marhazlinda; Palupi, Retno; Setyowati, Dini; Ramadhani, Aulia; Evany, Saphira Firdausi (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: COVID-19 is a global pandemic health problem that is getting a lot of attention around the world today. It is a serious illness that can significantly affect the daily lives of patients and their families in terms of mental health problems, such as post-traumatic stress, depression, anxiety, and insomnia, as well as negatively impacting the quality of patients. Purpose: This study aims to determine the impact of long haulers on the quality of life of COVID-19 survivors in East Java, Indonesia. Methods: Researchers conduct detailed the solution to overcome the problem by using educational videos and sports or routine gymnastics to change the attitude of COVID-19 survivors towards long haul healing is done through the distribution of the two facilities via the google drive link. The drafting team has 2 program plans as a solution to the problems carried out. Results: The prevalence of COVID-19 survivors with long haulers was slightly higher than that of non-long haulers. The results of the knowledge and attitude scores on the pre-test and post-test after viewing the media booklet and educational video showed a significant difference and improvement of quality of life in the result. Conclusion: The level of knowledge, attitudes, and quality of life including the physical health of long haul COVID-19 survivors in East Java experienced a significant increase after being given counseling through online booklets andeducational videos.